An assessment of the contribution of apiculture to household income and food security: case study of ward 20, Chirumhanzu district, Zimbabwe - Manuhwa, Trevor (Midlands State University, 2017)
The study assesses the contribution of apiculture to household income and food security in Ward 20, Chirumhanzu District. A mixture research design was adopted that is it used both qualitative and quantitative data collection techniques. Data was collected through the use of questionnaires, observations and interviews. Questionnaires were administered to all participants that is a target population of fifty households constituting both males and females who were participating in apiculture. Interviews were conducted with the key informants from Allied Timber Officer, Forest Commission officer, AGRITEX and the Ward councillor. The research findings show that they are three major factors which are influencing people to participate in apiculture. These are source of income and food, availability of forest and bees and as a hobby. The study also found out that apiculture contribute to food security to a larger extent since the results showed that above 90% of the people participating are now food secure and are having at least two or more meals a day. In comparison with the households not participating, the research results reflected that households doing apiculture have more food for survival throughout the year. The factors which are affecting apiculture in Chirumhanzu Ward 20 are heavy rains and heat waves due to climate change, theft and financial backbone. The overall conclusion is that households participating in apiculture have improved their living standards through income generation and improved healthy and diet. Recommendations were made on how best the government and the local people can take advantage of apicultural projects and utilize them to a maximum level to ensure absolute household food security and income generation.